Quality of school-based prevention programs: results from a national survey - Gottfredson, Denise C. (Journal of research in crime and delinquency, 2002)
A national probability sample of 3,691 school-based prevention activities operating in the spring of 1998 is used to describe the quality of implementation of typical school-based prevention practices, compare the quality of implementation of prevention practice with what is typical in prevention research, and test hypotheses about predictors of the quality of implementation. Results indicate that the quality of school-based prevention practices as they are implemented in the typical school is low. The examination of correlates of prevention quality suggests that the level of implementation of prevention practices can be improved through better integration of these activities into normal school operations; more extensive local planning and involvement in decisions about what to implement; greater organizational support in the form of high-quality training, supervision, and principal support; and greater standardization of program materials and methods. Implications for practice are discussed